ADAPTASI BIOMOLEKULER HIPERTROPI JARINGAN OTOT RANGKA PADA LATIHAN BEBAN DAN MANFAATNYA PADA SINDROMA METABOLIK - I Putu Adiartha Griadhi (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2019)
ABSTRACTWeight training is one of the exercises needed to achieve physical fitness. This exercise can increase muscle mass and metabolic function of the muscles so that it becomes an important exercise in the condition of the metabolic syndrome. Muscle is the largest hormone-sensitive tissue in the human body, this tissue consumes a lot of oxygen and consumes most of the glucose through the mediation of insulin. Weight training results in hypertrophy or increase in muscle mass and hyperplasia or increase in the number of muscle cells. Various biomolecular mechanisms can explain the hypertrophy and hyperplasia processes including the anabolic mTOR pathway, the catabolic pathway myostatin - Smad and the repair pathway by Satellite Cells. Understanding of the biomolecular process can provide a theoretical foundation in developing a weight training program so that the exercise becomes effective and safe.Keyword : weight training, metabolic syndrom, muscle hipertrophy